2600 commons collaborative spaces for the Baguio City community - Acosta, Darren Daniell M. (College of Architecture, University of the Philippines Diliman, 2018)
Baguio City government envisions the city to be a center for education, trade, and family-oriented tourism and strive to make initiatives towards creating a sustainable and enabling environment. The project, 2600 Commons, aims to break the norm of Baguio City developments that are commonly aligned towards tourism and commercialization, which is currently creating contradictions to what the Baguio City community really needs. Baguio City is more than just a tourist destination. This gives light to the potential of the City, other than being the Summer Capital of the Philippines, as the Education Center of the North where it focuses on the potential of developing something that would retrofit to the needs of majority of the Baguio City community- that is the students and the working class. It also aims to address the prevalent over-development issue of the city by refocusing developments towards alleviating today's issues- road congestion. This project aims to bring Baguio City as a walkable and healthy city while highlighting the essence of commuting as part of Baguio City locals' culture and a way to help alleviate congestion problems at the nodes of the city proper, which are commonly rooted towards use of private vehicles. With that, the project aims to promote commuting through an efficient commuting system that would lessen dependence on private vehicles as well as promoting awareness and responsibility for Baguio City visitors. What Baguio City needs are public spaces, not malls.